AI-Enabled Digital Transformation of Total Rewards in HR 4.0 Leading to Sustainability - Varsha, Puja (Digital Repository of Theses - SSBM Geneva, 2025)
This paper delves into the transformative potential of integrating artificial intelligence (AI) into Total Rewards strategies within the context of HR 4.0, where emerging technologies are reshaping human resource practices across industries. It explores how AI can revolutionize traditional compensation models by enhancing their flexibility and responsiveness to the dynamic needs of the workforce. By harnessing the power of AI, organizations can create data-driven compensation systems that adapt to changing market conditions, employee performance, and business objectives. This allows companies to move beyond one-size-fits-all compensation approaches, offering tailored reward packages that resonate with individual employee aspirations and organizational priorities. Beyond technological advancements, the paper also addresses the broader theme of sustainability in HR practices. It examines how AI can contribute to the creation of sustainable and ethical compensation frameworks, ensuring that pay decisions are fair and aligned with long-term organizational goals. As organizations increasingly prioritize equity and transparency in their compensation practices, AI offers powerful tools to enhance these efforts by reducing bias, ensuring pay equity, and providing real-time insights into workforce dynamics. Through a detailed analysis of AI’s impact on compensation within Total Rewards, this study highlights the potential of AI to not only drive innovation but also support organizations in making more sustainable compensation decisions. The research contributes to the ongoing discussion on leveraging technology to build compensation systems that foster organizational success. Ultimately, this paper provides a framework for adopting AI-driven compensation strategies that align with both the evolving demands of the workforce and the broader strategic objectives of the organization in the HR 4.0 era.